Radiological measurement of cochlear dimensions in cochlear hypoplasia and its effect on cochlear implant selection - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2021)
Objective To determine the effect of cochlear dimensions on cochlear implant selection in cochlear hypoplasia patients. Methods Temporal bone computed tomography images of 36 patients diagnosed with cochlear hypoplasia between 2010 and 2016 were retrospectively reviewed and compared with those of 40 controls without sensorineural hearing loss. Results Basal turn length and mid-modiolar height were significantly lower in the cochlear hypoplasia patients with subtypes I, II and III than in the control group (p < 0.001). Mid-scalar length was significantly shorter in subtype I-III patients as compared with the control group (p < 0.001). In addition, cochlear canal length (measured along the lateral wall) was significantly shorter in subtype I-IV patients than in the control group (subtypes I-III, p < 0.001; subtype IV, p = 0.002) Conclusion Cochlear hypoplasia should be considered if basal turn length is less than 7.5 mm and mid-modiolar height is less than 3.42 mm. The cochlear implant should be selected according to cochlear hypoplasia subgroup. It is critically important to differentiate subtype II from incomplete partition type I and subtype III from a normal cochlea, to ensure the most appropriate implant electrode selection so as to optimise cochlear implantation outcomes.
Keywords: Cochlear Implantation; Hearing Loss; Sensorineural; Ear; Inner; Cochlear Diseases; ELECTRODE INSERTION; INNER-EAR; CLASSIFICATION; LENGTH; DEPTH